P419 Patterns of group sex activity among gay and bisexual men in melbourne and sydney in australia, 2013–2018. (14th July 2019) - Chow, Eric; Lea, Toby; Fairley, Christopher; Mao, Limin; Broady, Timothy; Bavinton, Benjamin; Prestage, Garrett; Holt, Martin
Abstract : Background: This study analysed trends in group sex among gay and bisexual men (GBM) and the factors associated with group sex. It is important to understand GBM who engage in group sex as they may be at risk of and require more intensive screening for sexually transmitted infections (STI). Methods: The Gay Community Periodic Surveys are annual behavioural surveys of GBM. We analysed data collected from Melbourne and Sydney during 2013–2018. Participants were eligible if they were ≥16 years, male, and reported sex with men in the last 5 years. We calculated trends in group sex (sex involving at least two other men) in the last 6 months and used multivariable logistic regression to identify factors associated with it. Results: Among 31, 341 GBM, the proportion engaging in group sex increased from 30.9% in 2013 to 36.8% in 2018 (ptrend <0.001). Group sex was associated with having ≥10 male partners in the last 6 months (aOR: 3.63; 95% CI: 3.38–3.90), using Viagra (aOR: 1.40; 95% CI: 1.29–1.52) and testing for HIV/STI in the last 12 months (aOR: 1.36; 95% CI: 1.25–1.47). Compared with HIV-negative GBM who did not use PrEP (n=23, 003), HIV-negative GBM who used PrEP (n=2, 299; aOR: 1.57; 95% CI: 1.39–1.77) and HIV-positive GBM (n=2, 701; aOR: 1.15; 95% CI: 1.03–1.28) were more likely to report group sex. GBM who met male partners at private sex parties (aOR: 5.03; 95% CI: 4.30–5.89) and saunas (aOR: 2.34; 95% CI: 2.17–2.51) had the highest odds of engaging in group sex. Conclusion: Group sex has become more common among GBM in Melbourne and Sydney over the last 6 years. While group sex is concentrated among PrEP users and HIV-positive GBM, there remains a large group of non-PrEP-users who engaged in group sex and would benefit from regular STI screening (and potentially the offer of PrEP). Disclosure: No significant relationships.